COMMERCIALIZATION OF GM CROPS: A THREAT TO THE ENVIRONMENT SAFETY AND SUSTAINABILITY? - SMITA SAHU; NITYA SHARMA (International Journal of Pharma and Bio Sciences, 2015)
The introduction of GM crops on a large scale has inadvertently impacted the environment either through escapes or gene flow from such crops into the natural environment, or through the changes in agricultural practices. This paper extensively sensitizes the regulatory framework for commercialization of genetically modified crops and the environmental impact of GM crops and has outlined ways in which such crops may influence the biodiversity, genetic diversity and environmental components, and also raises further concern on what right we have to manipulate creation in this way highlighting the significance of biotechnology in revamping agro biodiversity scenario and whether or not the process of Genetic Modification itself is permissible and tantamount to play against the creation ‘of the God’ and ethical acceptance of patents associated with novel gm crops with respect to the correlation of intellectual property rights and commercial viability. There have been a lot of ethical, social and legal questions about the acceptability of genetic modification of nature and limitations in our current scientific levels of understanding clearly how, genetic modifications amounted to the complex natural entities with a ‘blunt instrument’ and that it would be impossible to predict the outcomes of such manipulations resulting in the unacceptable consequences.